The Shadow State Narrative, Bureaucratic Politics, and National Resilience in the Trump Era - Fahlesa Munabari; Margaretha Hanita; Abdul Rivai Ras (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: The purpose of this paper is to examine the relationship between the first term of the Trump administration (2017–2021) and the United States Intelligence Community (USIC), with particular attention to intelligence politicisation, bureaucratic politics, and the deployment of the “deep state” narrative. The authors argue that these dynamics are changing patterns of democratic governance and impacting the national resilience of the United States in the realms of politics, government, and security. Study Design/Methodology/Approach: This study adopted a qualitative approach to analyze the implementation of inter-institutional competition, while a national resilience framework based on the Asta Gatra framework was used to assess the interaction between political authority, administrative integrity, and security governance. Findings: Persistent distrust, populist rhetoric, and political intervention characterise the relations between President Trump and the Intelligence Community. These dynamics weakened analytical independence, institutional coordination, and transparency, thereby disrupting the balance between political and administrative resilience and constraining the state’s adaptive capacity in managing national security under political turbulence. Originality/Value: This study contributes to the literature by integrating bureaucratic politics and national resilience perspectives to reinterpret the Trump-Intelligence Community conflict as a test of institutional resilience, rather than a conspiracy phenomenon.